Anti‐TNF‐α for necrotizing sarcoid granulomatosis of the liver. Issue 4 (3rd February 2017) - Sebode, Marcial; Weidemann, Sören; Wehmeyer, Malte; Lohse, Ansgar W.; Schramm, Christoph
Abstract : We present a case of hepatosplenic necrotizing sarcoid granulomatosis, a variant form of "classical" sarcoidosis, that became clinically apparent in the form of multiple hepatic and splenic masses mimicking malignancy. Flow cytometry of intrahepatic T cells isolated from liver biopsy led to the targeted treatment with anti‐tumor necrosis factor‐alpha, which was highly effective in inducing remission. (Hepatology 2017;65:1410‐1412)